2002
DOI: 10.1093/annonc/mdf294
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of topotecan plus gemcitabine in the treatment of patients with relapsed ovarian cancer after failure of first-line chemotherapy

Abstract: Topotecan combined with gemcitabine has a favourable toxicity profile and encouraging efficacy in patients with recurrent ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 17 publications
2
13
1
1
Order By: Relevance
“…Although single-agent topotecan is widely used for the treatment of relapsed ovarian cancer, combinations identified in this study may offer additional insights. The high degree of synergy that we reported previously for topotecan/ gemcitabine in ovarian cancer specimens (Su et al, 2001) is supported by the results of a phase II study, in which seven of 11 (64%) patients with relapsed ovarian cancer achieved objective responses with this combination (Sehouli et al, 2001). Topotecan combinations might also be investigated in diseases that are historically resistant to chemotherapy.…”
Section: Discussionsupporting
confidence: 75%
“…Although single-agent topotecan is widely used for the treatment of relapsed ovarian cancer, combinations identified in this study may offer additional insights. The high degree of synergy that we reported previously for topotecan/ gemcitabine in ovarian cancer specimens (Su et al, 2001) is supported by the results of a phase II study, in which seven of 11 (64%) patients with relapsed ovarian cancer achieved objective responses with this combination (Sehouli et al, 2001). Topotecan combinations might also be investigated in diseases that are historically resistant to chemotherapy.…”
Section: Discussionsupporting
confidence: 75%
“…The drug has synergistic activity with platinum by forming platinum-DNA adduct which inhibits ribonucleotide reductase. Several clinical studies have demonstrated high efficacy of the combined drugs: RRs of 16-70% with cisplatin (Nagourney et al, 2003;Rose et al, 2003;Brewer et al, 2006;Bozas et al, 2007), 40% with paclitaxel (Garcia et al, 2004;Poole et al, 2006), 13-64% with topotecan (Greggi et al, 2001;Sehouli et al, 2002), or 34% with PLD (Ferrandina et al, 2005). Our study could not demonstrate any RR by a combination regimen in platinum-resistant patients except one patient who could achieve SD.…”
Section: Discussioncontrasting
confidence: 52%
“…Third was the regimen of gemcitabine. Some studies found RRs of 6-29% from single agent (Shapiro et al, 1996;Friedlander et al, 1998;D'Agostino et al, 2003;Markman et al, 2003;Mutch et al, 2007;Ferrandina et al, 2008;Watanabe et al, 2008;Suprasert et al, 2012;Yoshino et al, 2012) while others could demonstrate RRs of 13-70% from gemcitabine in combination with platinum or other agents (Greggi et al, 2001;Sehouli et al, 2002;Nagourney et al, 2003;Rose et al, 2003;Garcia et al, 2004;Papadimitriou et al, 2004;Ferrandina et al, 2005;Brewer et al, 2006;Pfisterer et al, 2006;Poole et al, 2006;Bozas et al, 2007). Another reason which might be under-recognized was the setting when gemcitabine was used or numbers of prior chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data have suggested that gemcitabine may have a possible role in overcoming platinum resistance by its inhibition of excision repair enzymes (84). The results of smaller phase II trials also suggest that either liposomal doxorubicin or topotecan administered in conjunction with gemcitabine improves tumor response rates compared with historical results observed with single agents (85,86). Gemcitabine is non-cross-resistant to other agents, is generally well tolerated, has an absence of cumulative toxicity, and is convenient.…”
Section: Gemcitabinementioning
confidence: 99%